2008
DOI: 10.2214/ajr.07.3483
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Papillary Lesions of the Breast: Clinical, Imaging, and Pathologic Correlation

Abstract: Recognition of the variety of benign and malignant papillary lesions of the breast will facilitate diagnosis and proper management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 14 publications
2
68
0
1
Order By: Relevance
“…Both may have microcalcifications because these lesions may infarct and/or become sclerotic with time. [3][4][5] On histologic examination, IDPs may have variable amounts of epithelium, from one to multiple layers. The epithelium is often of columnar morphology and/or displays usual ductal hyperplasia (UDH) and/or apocrine metaplasia.…”
Section: Intraductal Papillomamentioning
confidence: 99%
See 1 more Smart Citation
“…Both may have microcalcifications because these lesions may infarct and/or become sclerotic with time. [3][4][5] On histologic examination, IDPs may have variable amounts of epithelium, from one to multiple layers. The epithelium is often of columnar morphology and/or displays usual ductal hyperplasia (UDH) and/or apocrine metaplasia.…”
Section: Intraductal Papillomamentioning
confidence: 99%
“…The World Health Organization classifies these as tumors in situ, and they are managed accordingly. [2][3][4][5][6][7][8][9][10][11][12][13] However, recent publications have shown that most either completely lack myoepithelium, both within papillae and at the periphery or, less frequently, have very sparse myoepithelium at the periphery only. Because of this, authors have suggested that they likely represent a good-prognosis subtype of invasive carcinoma [14][15][16][17] or may, at least, be a lesion in transition.…”
Section: Encapsulated Papillary Carcinomamentioning
confidence: 99%
“…It generally occurs in women over 60 years old. Patients with papillary carcinoma often present a palpable central mass or bloody nipple discharge (6,7). It is characterized by slow growth and better prognosis compared to ductal carcinomas not otherwise specified.…”
Section: Papillary Carcinomamentioning
confidence: 99%
“…It is characterized by slow growth and better prognosis compared to ductal carcinomas not otherwise specified. The frequency of axillary nodal metastases is low (6,7). The mammographic appearance is a solitary round or lobulated, relatively circumscribed mass or clusters of masses (6,7), which may be associated with microcalcifications.…”
Section: Papillary Carcinomamentioning
confidence: 99%
“…5 Recent studies have demonstrated that MRI is more accurate than mammography in assessing invasive cancers for assessing local extent of disease. 6 Major duct excision is still considered the gold standard to exclude an underlying malignancy, but some authors have suggested that MRI might allow improved patient selection and treatment planning compared with conventional imaging (i.e.…”
Section: Introductionmentioning
confidence: 99%